Molecular Characterization of Unknown Potentially Salt Tolerant Olive Genotypes Using RAPD Markers (Journal of Sciences, Islamic Republic of Iran)
Randomly amplified polymorphic DNA (RAPD) markers were used to study the genetic diversity and discriminate among 17 unknown genotypes (considered potentially salt tolerant) and 16 known olive cultivars. Fifteen decamer primers which produced 38 reproducible polymorphic bands in the genotypes were selected for analysis. The RAPD markers resulted in 93 distinct banding patterns. Based on either unique or combined patterns all genotypes could be identified. Genetic similarities between genotypes were estimated using Jaccard's similarity index indicating a high degree of diversity within the known and unknown genotypes. Using the unweighted pair-group method (UPGMA), most genotypes were clustered into two main groups according to their origin area of cultivation (native and foreign ones). The unknown genotypes mainly clustered with cv. Zard, one of the native Iranian olive cultivars. The presented results contribute to a comprehensive understanding of unknown olive genotypes, which potentially are tolerant to the high salinity of their cultivation area. These genotypes could be important for extension of cultivation purposes and breeding programs